7-Endo-trig Pictet–Spengler type cyclization of 5-alkylidene/arylidene-amino-3H-pyrimidin-4-ones: An efficient and diastereoselective synthesis of pyrimido[4, 5-b] [1, 4]benzodiazepines. Issue 8 (18th April 2021) - Naikoo, Rayees Ahmad; Kumar, Rupesh; Singh, Parvesh; Bhargava, Gaurav
Abstract: The manuscript describes an efficient, atom economical synthesis of pyrimido[4, 5-b][1, 4]benzodiazepin-4-ones by relatively unexplored 7- endo-trig Pictet–Spengler type cyclisations. The synthetic methdodlogy involves the synthesis of different variants of 5-arylidene-amino-3H-pyrimidines and their p- toluene sulfonic acid mediated 7- endo-trig Pictet–Spengler type cyclisations to afford biologically relavent functionalized benzodiazepine condensed pyrimidinones such as pyrimido[4, 5-b][1, 4]benzodiazepines in good to excellent yields (82–94%). Graphical Abstract: UF0001